Fortællinger om et liv som arbejdsløs og socialt ekskluderet - Larsen, Eva Ladekjær; Andersen, Pernille Tanggaard; Bak, Carsten Kronborg (Tidsskrift for Forskning i Sygdom og Samfund, 2012)
We live in a modern society where working life both is a source to identity and wealth and at the same time occupy our time and energy. But how is it to be unemployed and excluded from this working community? And why is it so hard to reintegrate people at the labour market? Based on theory of social exclusion these questions are explored by analysing socially vulnerable citizens’ everyday lives and the complex social problems that have been accumulated through out their lives. We demonstrate how these accumulated risk profiles create barriers to be included in working life and often involves a high degree of marginalisation.